2012
DOI: 10.1007/s10854-012-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide-fullerene nanostructured materials for nonlinear optics and solar energy applications

Abstract: Based on the model polyimide systems the principal nonlinear optical features, such as laser induced refractive indices changes, nonlinear refraction and third order susceptibility have been established during their doping with fullerenes, shungites, carbon nanotubes, carbon nanofibers, quantum dots, etc. The evidence of the correlation between laser induced refractive indices and charge carrier mobility has been obtained. The features of new nanocomposites for their possible optoelectronics, laser techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…A detailed study of the refractive properties of the fullerene sensitized LC has permitted to propose the model connected with the increased dipole moment via increased barrier free electron pathway and the number of the delocalized charge at fullerene molecules. This model has been shown in the paper [74] and extended using other nanoparticles as promising intermolecular sensitizers in the papers [75][76][77]. It has been shown that in such sensitized organic conjugated systems the pathway of the charge transfer carrier is changed due to a fact that charge transfers from the intramolecular donor fragment of organic conjugated molecules (such as polyimide, polyaniline, pyridine, etc.)…”
Section: Obtained Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A detailed study of the refractive properties of the fullerene sensitized LC has permitted to propose the model connected with the increased dipole moment via increased barrier free electron pathway and the number of the delocalized charge at fullerene molecules. This model has been shown in the paper [74] and extended using other nanoparticles as promising intermolecular sensitizers in the papers [75][76][77]. It has been shown that in such sensitized organic conjugated systems the pathway of the charge transfer carrier is changed due to a fact that charge transfers from the intramolecular donor fragment of organic conjugated molecules (such as polyimide, polyaniline, pyridine, etc.)…”
Section: Obtained Results and Discussionmentioning
confidence: 93%
“…It is connected with the change of the laser induced refractive index and, as a result, the existence of the energy losses due to diffraction on the nanostructured compounds can be included in the explanation of the OL effect. The obtained 3D picture is firstly shown in papers [77,85] and is now presented in the modified version in Fig.5. It should be mentioned that this modified version of the diffraction picture is connected with the large number of results obtained for the structured conjugated organics materials via fourwave mixing laser technique and repeated so many times.…”
Section: Obtained Results and Discussionmentioning
confidence: 99%
“…Thus, laser-matter interaction provokes the change in polarization of the media and predicts the change in such properties as dynamic, photorefractive and photoconductive ones. To predict the change of the cubic nonlinearity  (3) , as the minimum media local volume polarizability (Kamanina, 2005, Kamanina & Uskokovic, 2008, Kamanina et al, 2012, the laser-induced change of the refractive index ni can be calculated from the diffraction efficiency  (Kamanina et al, 2015, Akhmanov & Nikitin, 1997 via realization of the Raman-Nath diffraction conditions ( -1 d) using the equation ( …”
Section: Experimental Conditions Materials and Results: Organicmentioning
confidence: 99%
“…The peculiarities of the growth, the mechanisms of the sensitization, and the changes of the basic physic-chemical parameters have been tested. Our own steps in this direction occupy a significant place too (Kamanina, 2002, Kamanina, 2005, Kamanina & Uskokovic 2008, Kamanina et al, 2012, Kamanina et al, 2016. The main reason to use fullerenes, shungites, and quantum dots is connected with their unique energy levels and high value of electron affinity energy.…”
Section: Introductionmentioning
confidence: 99%
“…It should be said that the calculated values of nonlinear refraction n 2 and third-order nonlinear susceptibility χ [30,31,[34][35][36]. The growth of refractive coefficients correlated with the change of the photoconductive (increase of mobility of charge carriers), and it is connected with the changes in the order parameter of the studied materials and with the infrared shift of their spectral characteristics.…”
Section: Nanomechanicsmentioning
confidence: 93%